Evaluation of the forces applied by rubber dam clamps on mandibular first molar teeth with different endodontic access cavities: a 3D FEA study - Eskibaglar, Mehmet; Erdem, Serkan; Eskibaglar, Busra Karaagac; Kaman, Mete Onur (Peerj Inc, 2024)
Background: This study aimed to examine the effect of the force applied by rubber dam clamps made from different materials on mandibular fi rst molar teeth with various designs of endodontic access cavities using fi nite element analysis. Methods: A intact tooth (IT) and seven different endodontic access cavities namely, a traditional endodontic cavity (TRADAC), a guided endodontic cavity (GEC), a conservative endodontic cavity (CAC), an ultra-conservative access cavity (UAC), a truss access endodontic cavity (TRSAC), a mesial caries access cavity (MCAC), and a distal caries access cavity (DCAC), along with two different clamp fi nite element models, were created. The clamp models were made of polyether ether ketone (PEEK) and stainless steel (SS). The forces applied by the clamps were calculated based on the axial section distance of the tooth, and these forces were applied to the contact areas on the tooth. Stress distribution models were calculated using maximum von Mises (vM) stress. Results: The lowest vM stress under the forces applied by the SS and PEEK clamps was found in the IT model (80.914 MPa) with the PEEK clamp. The highest vM stress was found in the DCAC model (759.49 MPa) applied with the SS clamp. The forces applied by SS clamps resulted in higher vM stress values in every cavity design than those applied by PEEK clamps. Conclusion: PEEK clamps generated less force than SS clamps. However, clinicians should follow various isolation strategies (clamp made of different materials, split dam, etc .) according to different cavity types of the tooth.
Keywords: Corresponding author; Endodontic access cavity; Finite element analysis; Isolation; Rubber dam clamp